A universidade e o desafio de escrever para professores - Vilaronga, Carla Ariela Rios; Sarti, Flavia Medeiros [UNESP] (Universidade Federal do Rio Grande do Sul - Faculdade de Educação, 2012)
The article broaches processes relating to the production of texts aiming primary education teachers, focusing both function and role of the authors on these texts. In the present educational context, the authors of these papers perform an important purpose as their actions integrates the legitimation of specific discourses and new modalities of teacher formation. These academic researchers come across new challenges, e.g. writing for school teachers. The study which data is presented in this article was accomplished under a qualitative approach, starting with documentary analysis, and interviews, having as an empiric reference a special program for graduated working teachers.

O artigo discute aspectos relacionados à produção de textos dirigidos a professores da Educação Básica, focalizando a função-autor nesse processo. No contexto educacional atual, os autores desses textos desempenham importante papel, à medida que sua atuação integra-se a processos de legitimação de certos discursos e de novas modalidades de formação docente. Esses pesquisadores acadêmicos se deparam com novos desafios, entre eles o de escrever para os professores da escola. O estudo cujos dados são apresentados neste artigo foi realizado sob uma abordagem qualitativa, a partir de análise documental e de entrevistas, tendo por referencial empírico um programa especial de formação superior de professores em serviço.
The university and the challenge of writing for teachers
Keywords: Teacher; Universitarization of teaching; Teacher professionalization; Special programs; Authorship; Formação de professores; Universitarização do magistério; Profissionalização docente; Programas especiais; Autoria